Efficacy of transdiagnostic cognitive-behavioral therapy for assertiveness: A randomized controlled trial - Tobias Hagberg; Patrik Manhem; Martin Oscarsson; Fiona Michel; Gerhard Andersson; Per Carlbring (Internet Interventions, 2023)
Assertiveness training has been an essential component in cognitive-behavioral therapy (CBT), for example, in the treatment of social anxiety and in dialectical behavioral therapy. However, the assertiveness construct has garnered little attention in recent clinical research. The objective of this study was to investigate the efficacy of an eight-week transdiagnostic stand-alone internet-based CBT intervention specifically aimed at increasing levels of assertive behavior. Following inclusion, we randomized N = 210 participants into three groups: therapist-guided self-help, unguided self-help, and a wait-list control condition. After a one-year follow-up, we employed a linear mixed model to estimate the effects at both post-test and follow-up for the primary outcome measures of assertiveness, Adaptive and Aggressive Assertiveness Scales, the Rathus Assertiveness Schedule, and secondary outcome measures of anxiety, depression, and general well-being. We also assessed reliable clinical change. Compared to the wait list at the post-treatment, estimated between-group effect sizes on self-rated adaptive assertiveness were statistically equivalent for the two treatment groups both at the post and at the one-year follow-up time points, ranging from ES = 0.95 to 1.73, with reliable clinical recovery proportions from 19 % to 36 %. The increase in aggressive assertiveness ranged from ES = 0.62 to 0.90 compared to the wait-list condition at post. For social anxiety symptoms, the effects compared to the wait list at post-treatment ranged from ES = 0.67 to 0.93, with a reliable clinical recovery rate from 16 % to 26 %. For self-assessed well-being, the effects compared to the wait list at post ranged from ES = 0.70 to 1.05. No effects were observed for generalized anxiety, although within-group evidence was found for a medium effect on depression one year after treatment. Overall, the two treatment conditions produced similar effects. In general, participation increased healthy assertive expressions regardless of treatment condition, all the while reducing self-assessed social anxiety and, over time, possibly also depression. Participation also improved general well-being. The findings demonstrate that the assertiveness construct can be a suitable target for intervention, with reductions of both psychiatric symptoms and non-syndromal problems in daily life. The study was preregistered at ClinicalTrials.gov (NCT04240249).